2010
DOI: 10.3389/fnhum.2010.00233
|View full text |Cite
|
Sign up to set email alerts
|

Why is that Hammer in My Coffee? A Multimodal Imaging Investigation of Contextually Based Tool Understanding

Abstract: Appropriate tool–object pairing is a natural part of our lives. When preparing to stir coffee, we know that a hammer is useful for some tasks but that it is not appropriate in this behavioral context. The neural correlates of this context–tool pairing process remain unclear. In the current work, we used event-related electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) to determine neural correlates for differentiating contextually correct and incorrect tool use. Subjects were shown im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…empty or full; with or without the nutshell). A neuroimaging and EEG study (Mizelle and Wheaton 2010) has shown that the contextual correctness/ incorrectness of tool-object interaction activated distinct brain regions. Specifically, incorrectness activated temporal area, cingulate area and insula, whereas correctness activated parietal and frontal areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…empty or full; with or without the nutshell). A neuroimaging and EEG study (Mizelle and Wheaton 2010) has shown that the contextual correctness/ incorrectness of tool-object interaction activated distinct brain regions. Specifically, incorrectness activated temporal area, cingulate area and insula, whereas correctness activated parietal and frontal areas.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in accordance with the concepts of compatibility, suitability and actual state of artefacts proposed for working affordances. Indeed, Mizelle and Wheaton (2010) suggested that activation of insula and superior temporal cortex may serve as a ''gatekeeper'', for the evaluation of the contextual correctness of possible interactions between presented artefacts (e.g. bottle with empty glass).…”
Section: Discussionmentioning
confidence: 99%
“…; Perini et al. ), while more anterior regions of the MTG are recently associated with knowledge about a tool's use, such as tool‐recipient matches and mismatches (Mizelle and Wheaton ,b), and other tool‐related semantic knowledge (Ishibashi et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The temporal window of coherence analysis of interest was based on the detailed theoretical methodology in this previous work. This work focused on the time of ~400 ms (280-526 ms, centered at 408 ms), based on prior studies showing that neural responses related to comprehension of skilled action occur within the first 400 ms of the image presentation (Mizelle & Wheaton, 2010). Also, due to multiple factors involving decision making possibly influencing the neural networks at a later time window, we sought after the time window of the earliest response to the image.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%